2016
DOI: 10.1158/0008-5472.can-15-1443
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Anti-VEGF Therapy Mediated by Autocrine IL6/STAT3 Signaling and Overcome by IL6 Blockade

Abstract: Anti-VEGF therapies benefit several cancer types, but drug resistance that limits therapeutic response can emerge. We generated cell lines from anti-VEGF-resistant tumor xenografts to investigate the mechanisms by which resistance develops. Of all tumor cells tested, only A431 (A431-V) epidermoid carcinoma cells developed partial resistance to the VEGF inhibitor aflibercept. Compared with the parental tumors, A431-V tumors secreted greater amounts of IL6 and exhibited higher levels of phospho-STAT3. Notably, c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…A number of studies have revealed that IL-6 was released by autocrine and paracrine by malignant cells or immune cells and functioned in tumorigenesis [40, 46, 47]. Generally, IL-6 was secreted by noncancer stem cells in low-attachment culture conditions and enriched Oct4 gene expression by activating the IL-6R/JAK/STAT3 signaling pathway in chronic inflammatory disease, such as cholangiocarcinoma [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have revealed that IL-6 was released by autocrine and paracrine by malignant cells or immune cells and functioned in tumorigenesis [40, 46, 47]. Generally, IL-6 was secreted by noncancer stem cells in low-attachment culture conditions and enriched Oct4 gene expression by activating the IL-6R/JAK/STAT3 signaling pathway in chronic inflammatory disease, such as cholangiocarcinoma [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-associated adipocytes can also promote radio-resistance by secreting IL-6 [158], whilst IL-6 and IL-8 secreted by mesenchymal stem cells activate macrophages in the microenvironment of human colorectal and ovarian cancers, causing chemoresistance [159,160]. Besides causing resistance to chemo-and radiotherapy, autocrine secretion of IL-6 (induced by therapy) also confers resistance to some targeted therapies; for example, aflibercept (anti-VEGF, inhibitor)-resistant epidermoid carcinoma cells and herceptin (trastuzumab, anti-HER2)-resistant breast cancer cells secrete a large amount of IL-6 and show hyperactivation of STAT-3 signalling, causing resistance to therapy [161,162].…”
Section: Il-6 Induces Therapeutic Resistance In Cancermentioning
confidence: 99%
“…Tocilizumab has been shown to improve cachexia developed by IL-6 overexpression in lung cancer patients [175]. The combination of anti-IL-6R with herceptin and aflibercept enhances therapeutic gain, also in targeted therapy-resistant breast cancer and epidermoid carcinoma, respectively [161,162]. However, blocking IL-6 signalling can be harmful and may result in some adverse effects, such as gastrointestinal, nasopharyngeal and upper respiratory tract infections, gastrointestinal haemorrhage, thrombocytopenia and neutropenia [198].…”
Section: Il-6 Induces Therapeutic Resistance In Cancermentioning
confidence: 99%
“…While no specific HIF1a blockers have been tested in this population, it is an active area of research. Preclinical models suggest that IL-6 blockade could be another mechanism to overcome resistance to VEGF therapy mediated by changes in the microenvironment (75).…”
Section: Hif-1αmentioning
confidence: 99%